2007
DOI: 10.1016/j.ddmod.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Models of gender differences in cardiovascular disease

Abstract: Clinical observations made over several decades support the existence of gender differences in cardiovascular disease prevalence and severity. For example, women exhibit a delay in the onset of vascular disease compared to men and the temporal link between menopause and the rise in vascular events in women suggests that ovarian hormones may be important in reducing the risk of vascular disease in women. Gender differences have also been observed in the severity and outcome of myocardial diseases such that wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 42 publications
(44 reference statements)
0
27
0
Order By: Relevance
“…There is good reason to believe that the pharmacological effects of individual drugs may be different in men and women. A review of models of sex differences in various cardiovascular diseases concluded that a large number of physiological responses in animal models differ between sexes and that these cardiovascular responses are regulated by sex steroid hormone receptors [58]. Interestingly, the effect is not uniform.…”
Section: Survival Benefit From Individual Classes Of Drugs According mentioning
confidence: 99%
“…There is good reason to believe that the pharmacological effects of individual drugs may be different in men and women. A review of models of sex differences in various cardiovascular diseases concluded that a large number of physiological responses in animal models differ between sexes and that these cardiovascular responses are regulated by sex steroid hormone receptors [58]. Interestingly, the effect is not uniform.…”
Section: Survival Benefit From Individual Classes Of Drugs According mentioning
confidence: 99%
“…There is increasing evidence that the risk factors, causes, and clinical manifestations of various metabolic diseases are influenced by sex. Adult men are more susceptible to obesity, cardiovascular diseases and glucose metabolism abnormalities than premenopausal women (Dorak & Karpuzoglu, ; Karpe & Pinnick, ; Patten, ; International Diabetes Federation, ). This phenomenon can be explained by the higher proportion of visceral adipose tissue found in the abdominal region of men in comparison with women.…”
Section: Introductionmentioning
confidence: 99%
“…However, the incidence and the progressive rate of cardiovascular disease are markedly higher in men when age‐matched with premenopausal women . Women exhibit a delay in the onset of vascular disease compared with men, and the temporal link between menopause and the rise in vascular events in women suggests that ovarian hormones may be important in reducing the risk of vascular disease in women . Clinical studies have shown that women who have had a hysterectomy have a higher prevalence and incidence of cardiovascular disease and hypertension (irrespective of age when the hysterectomy was performed), indicating that the lack of ovarian hormones is associated with a greater rate of cardiovascular disease .…”
mentioning
confidence: 99%